Вплив інгібітору тирозинових протеїнкіназ геністеїну на агробактеріальну трасформацію рослин - Федорчук, В.; Ємець, А.І. (Фактори експериментальної еволюції організмів, 2015)
Aims. Agrobacterium-mediated method of DNA transfer allows to introduce in plant a big genetic construction with
minimum effect on transferable gene sequence, and also it does not require special equipment. The interaction between
plant and agrobacterium is regulated by a variety of chemical signals that can effect on the bacterial virulence, however,
molecular mechanism of this still unclear. Therefore, improving agrobacterial transformation method and increasing
its efficiency remain extremely important. Methods. Agrobacterium-mediated method of DNA transfer was used to
investigate the effect of genestein on transformation frequency. Results. In our study was investigated an influence of
a set of genestein concentrations in the range from 1 to 100 µM on transformation frequency was investigated. We
observed 20, 60, 80, and 85 % transformation frequency, when inhibitor was applied at concentrations 10, 25, 50, and
100 µМ, correspondingly. It should be noted that transformation frequency of control plants was 75 %. Conclusions.
The influence of different concentrations of tyrosine protein kinases inhibitor genestein on frequency of Agrobacterium
-mediated transformation of Nicotiana tabacum leaf explants was investigated. It was established that the addition of
100 мM genestein into the medium for co-cultivation with agrobacteria led to the increase of the transformation rate up
to 85 %, while the control was within 75 %.
Keywords: Agrobacterium-mediated transformation, tyrosine protein kinase inhibitor, Nicotiana tabacum.